Analisis Pemanfaatan Media Visual (Motion Graphic) Dalam Sosialisasi Aplikasi Pelayanan Perizinan Terpadu Satu Pintu (PTSP) Online Di Batam - Nadya Nabila; Gerson Julyfer Parulian Tambun; Melsha Haq Zulfikar (Politeknik Negeri Batam, 2019)
PTSP (One Door integrated licensing service) Online is a website based service application. This service application is intended for Batam City community who want to open business. However, there are still many people who do not know about the application of PTSP (Integrated One Door licensing service) based online. Such as not knowing the procedure of Online registration for both individuals and foundations or companies. There is a socialization media that helps the community to know the procedures for online registration of the application PTSP (Integrated one Door licensing service) Online. Motion graphic is a combination of 2D graphic and animation design that contains complete images, text, and sound as a means of visual media. This research implements Hannafin and Peck methods consisting of three stages of need analysis, stage of design and stage of development and implementation.Based on the analysis conducted based on the results of measurement success rate through the filling of the questionnaire and obtained the test result that there is a significant difference (meaning) in tests conducted on 30 respondents An increase of 0831. In T tests of a significant 0.05 (5%) Acquired Figure Sig. (2-tailed) 0.000 where 0.000 < 0.05 which means the knowledge of respondents related to PTSP online is increased after seeing the Motion Graphic